Use of the international classification of diseases (ICD)-11 method applied to veterinary forensic pathology for coding the cause and manner of death in wildlife - Marchetti, Cristina; Cantoni, Anna Maria; Ferrari, Luca; Pisani, Giovanni Maria; Corradi, Attilio (Frontiers in Veterinary Science, 2022)
The growth of human population has led, in recent years, to increasingly frequent contacts with the wild animals with which we share the territory, sometimes leading to negative interactions with them. The purpose of the study is to apply the codes contained in the 11th Revision of the International Classification of Diseases (ICD-11) method to investigate the cause and the manner of death, also to entrust the veterinarian with the task of recognizing and describing a suspected animal abuse as a sentinel indicator of violence towards humans and non-humans, thus expanding the concept of “One Health” from a forensic investigation perspective. The subjects recruited are wild mammals submitted for autopsy to the Pathology Unit of the Department of Veterinary Science, University of Parma, Italy, from 2015 to 2018. The manner and the cause of death of 167 wild animals of 16 different species have been investigated. When possible, an on-site inspection where the corpse was found was performed. Injuries were classified according to the on-line 11th Revision of the International Classification of Diseases method. Section 22 (Injury, poisoning or certain other consequences of external causes) was used to record the “immediate cause of death” (cause of death) and Section 23 (External causes of morbidity or mortality) was used to record the “underlying cause of death” (manner of death) for each animal. In most cases, death occurred as a result of road trauma but in some cases, abuse and voluntary killing were investigated. The recognition of non-accidental injuries is particularly important for both the defense in court of animals and for the connection between crimes committed against animals and against humans, known as “The Link”. The use of the ICD-11 method, as a sort of summary of the autopsy report, was confirmed to be of great value for the clarity and simplicity of processing the data collected also by veterinary pathologists. The veterinary pathologists can use this evidence-based method with the aim of creating a national register and therefore, to understand the real extent of the human impact on wildlife and document it in a scientific and statistically usable way.